Empowering Youth: A Qualitative Review on the Impact of Leadership and Participation on Biopsychosocial Development - Sennang, Indo; Alfina, Irma (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This study explores the impact of youth involvement in social activities, leadership, and sports on their biopsychosocial development. Various studies show that active participation in these activities can enhance self-esteem, emotional resilience, and mental well-being, as well as develop social and decision-making skills. However, while many studies have discussed the positive impact of leadership on psychosocial development, the understanding of the interaction between biological, psychological, and social factors remains limited. Using a qualitative approach through a literature review, this study aims to identify how youth participation in social and leadership activities can comprehensively affect their development. The findings of the study show that leadership and social participation significantly contribute to building social skills, increasing responsibility, and strengthening youth's psychosocial resilience. The study also highlights the need for a more holistic biopsychosocial approach in supporting the well-being of youth, particularly those in vulnerable groups. Suggestions for future research include exploring cultural diversity in youth empowerment and developing broader biopsychosocial intervention models to support their mental and social health. The implications of these findings are important for designing more effective leadership programs that not only support leadership skill development but also consider the physical, mental, and social well-being of youth.